2020
DOI: 10.3389/fmicb.2020.595798
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of BfmR-Regulated Antimicrobial Resistance in the Extensively Drug Resistant (XDR) Acinetobacter baumannii Strain HUMC1

Abstract: Acinetobacter baumannii is a problematic pathogen due to its common expression of extensive drug resistance (XDR) and ability to survive in the healthcare environment. These characteristics are mediated, in part, by the signal transduction system BfmR/BfmS. We previously demonstrated, in antimicrobial sensitive clinical isolates, that BfmR conferred increased resistance to meropenem and polymyxin E. In this study, potential mechanisms were informed, in part, by a prior transcriptome analysis of the antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Similarly, both BfmR and BfmS mutations reduced A. baumannii's survival in a murine pneumonia model (28). BfmR and BfmS have also been implicated in controlling resistance to a variety of antibiotics, including penicillins, carbapenems, fluoroquinolones, aminoglycosides, and macrolides (20,25,29,30). Finally, we previously found that BfmR is required for A. baumannii to endure a variety of stresses, including desiccation, osmotic challenge, exposure to hydrogen peroxide, and starvation (31).…”
mentioning
confidence: 94%
“…Similarly, both BfmR and BfmS mutations reduced A. baumannii's survival in a murine pneumonia model (28). BfmR and BfmS have also been implicated in controlling resistance to a variety of antibiotics, including penicillins, carbapenems, fluoroquinolones, aminoglycosides, and macrolides (20,25,29,30). Finally, we previously found that BfmR is required for A. baumannii to endure a variety of stresses, including desiccation, osmotic challenge, exposure to hydrogen peroxide, and starvation (31).…”
mentioning
confidence: 94%
“…The pathogenicity of A. baumannii isolates analyzed in the present study is exacerbated by the presence of the abaI / abaR quorum sensing system which is involved in morphology, growth characteristics, biofilm formation, motility, resistance and virulence of these microorganisms [ 36 ]. In addition, in our A. baumannii we found two-component signal transduction system BfmRS , which seem to be implicated in the control of various virulence-related traits and acting as a global modulator of A. baumannii physiology [ 37 , 38 ]. It is well known that, A. baumannii showing a loss of BfmS results in a significant reduction of motility [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…MIC was also determined by measuring CFUs in wells at 24 h; the MIC as assessed by CFU was designated as the drug concentration that inhibited growth ± ½ log relative to the starting inoculum when measured at 24 h. Doses ranged from 0.050 µM to 50 µM for DSM161 and from 0.010 µM to 13 µM for DSM186. Time-kill assays were performed in the presence or absence of a fixed DSM drug concentration (DSM161 50 µM (17.5 µg/mL), DSM186 2.9 µM (1 µg/mL)) over time as described ( 44 ) and compared to meropenem 2.6 µM (1 µg/mL).…”
Section: Methodsmentioning
confidence: 99%